Domestically-Produced Monoclonal-Antibody-Based Means of Diagnosing Particularly Dangerous Infections - O. F. Kretenchuk (Проблемы особо опасных инфекций, 2022)
Currently, great significance is attached to the preparation of diagnostic drugs based on specific immunoreagents, which include monoclonal antibodies produced by hybridomas. The use of monoclonal antibodies is one of the important approaches for the detection of pathogens of particularly dangerous infections – anthrax, brucellosis, tularemia, plague, cholera, glanders, and melioidosis. The review presents the main achievements of Russian scientists on obtaining such experimental drugs, and also pays attention to those sets of monoclonal reagents that are authorized in the Russian Federation. To date, three sets of reagents for detecting the causative agent of anthrax (latex agglutination, immunochromatographic method, multiplex immunofluorescence analysis) have been registered in our country on the basis of monoclonal antibodies; four sets of reagents for identifying the causative agent of tularemia (latex agglutination, immunochromatographic method, multiplex immunofluorescence analysis, dot-variant of enzyme immunoassay); three sets for the detection of plague microbe (enzyme immunoassay and immune chromatographic tests); five sets for cholera vibrios (slide agglutination, immunofluorescence, immune chromatographic method and enzyme immunoassay); two sets for the diagnosis of glanders and melioidosis (immunofluorescence); kits for detecting brucella have not been registered, there are only singular experimental designs. The involvement of modern drugs based on monoclonal antibodies in the diagnosis of particularly dangerous infections will improve the quality and reliability of laboratory analysis.